U.S. Army special forces : airborne rangers - Burgan, Michael (Mankato, Minn. : Capstone Books, 2000)
Introduces the U.S. Army's Airborne Rangers, their history, mission, development, training, and equipment.
Includes bibliographical references and index.
8 - 10 years
Keywords: United States. -- Army -- Commando troops; United States. -- Army -- Airborne troops; Special forces (Military science) -- United States; Special forces (Military science)